Evaluasi Pembelajaran Jarak Jauh Masa Pandemi Melalui Model Cipp di SD Negeri 78 Birea Kabupaten Bantaeng - Karmila Karmila; Eka Fitriana HS; Nurhadifah Amaliyah; Waddi Fatimah (STKIP Andi Matappa Pangkep, 2022)
This study aimed to evaluate the results of distance learning during the pandemic at SD Negeri 78 Birea, whether it was effectively implemented or not. This research was descriptive qualitative research with data collection techniques: observation, interview, and documentation. The informants in this study were wight people, including one principal, four teachers, and three students. The results showed that the evaluation results of distance learning through the model (context, input, process, and product) were less effective. This is due to the lack of preparation for distance learning between teachers and implementation, the lack of infrastructure facilities owned by students and teachers such as cell phones, computers, and books, limited assignments, and overall learning outcomes decline.